Analisis Problematika Pembentukan Lingkungan Bahasa Arab : (Studi Kasus di Prodi PBA STAI Syaichona Moh. Cholil Bangkalan) - Djakfar, Fera Andriani (Qismul Arab: Journal of Arabic Education, 2022)
Learning Arabic for PBA students is not only sufficient to be conducted in the classroom, but there must be a special environment outside the classroom that supports the provision of language materials in the classroom.  Therefore, PBA STAI Syaichona Moh.  Cholil Bangkalan tries to create an Arabic environment from year to year.  However, this effort cannot be separated from the various problems, so the purpose of this research is not only to describe the process of formation of the Arabic language environment, but also to analyze the problems of creating an Arabic environment in PBA STAI Syaichona Moh.  Cholil Bangkalan.  This research is a qualitative research to explore existing problems directly and not only through the existing literature.  The results of this study are the creation of an Arabic speaking environment in PBA STAI Syaichona Moh.  Cholil Bangkalan is formed in a formal and informal manner.  While the problems in creating an Arabic speaking environment include an open campus environment, neighboring Islamic boarding schools and other non-Arabic speaking study programs, mother tongue interference, lack of motivation, lack of regulations for language offenders, no private dormitory for PBA students, lack of supervision from leadership, and absence of supporting funds.